2018
DOI: 10.18203/2394-6040.ijcmph20184016
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of diabetes among patients with type 2 diabetes mellitus attending a rural health and training center

Abstract: Background: Diabetes mellitus (DM), a major threat to both developing and developed countries, which can be easily prevented by lifestyle modifications. Because of lack of awareness, the occurrence of diabetes and its complications is showing a steady increase. Empowering the patients with knowledge about diabetic self-care is expected to have better outcome of the disease. Thus this study was planned to assess the awareness and knowledge about diabetes among the patients with type 2 diabetes mellitus attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…While measuring waist circumference, only 42.10% had less than were aware of the symptoms of T2DM. 8 The participants have good knowledge on symptoms of diabetes which is vital in early diagnosis and treatment. Those who are unaware of the symptoms of diabetes may not be able to seek the health care services in a timely manner and may suffer from complications of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…While measuring waist circumference, only 42.10% had less than were aware of the symptoms of T2DM. 8 The participants have good knowledge on symptoms of diabetes which is vital in early diagnosis and treatment. Those who are unaware of the symptoms of diabetes may not be able to seek the health care services in a timely manner and may suffer from complications of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…While the Type 2 DM awareness score of the students did not show a significant difference in those with diabetes in their family, it was found that the risk of diabetes was higher in those with diabetes in their family according to FINDRISK scores and showed a significant difference (p<0.05). Similarly, studies have shown that those with a family history of DM have a level of awareness of type 2 DM (7,19,35,36). In addition, studies have found that participants with a family history of DM exhibit better knowledge scores than those without a family history of DM (13,26,27,34).…”
Section: %: Percent N: Number R=correlation Analysismentioning
confidence: 98%
“…Similarly, a study by Muninarayana et al, assessing the prevalence and awareness of diabetes mellitus among 311 adults in rural areas of India, showed that 50% of participants were aware of diabetes [ 8 ]. Moreover, another study by Aljin et al, using a sample of 258 patients with type 2 diabetes in the Tamil Nadu state, showed that 63.1% of them had adequate knowledge regarding type 2 diabetes mellitus [ 9 ] However, a study by Mohan et al, assessing awareness and knowledge about diabetes among the general population, as well as among individuals with diabetes in 4 selected regions of India, revealed poor knowledge and awareness of diabetes, particularly in rural areas [ 10 ]. According to preliminary research, a gap or lack of knowledge of chronic diseases can increase morbidity and mortality rates [ 11 ].…”
Section: Introductionmentioning
confidence: 99%